2015
DOI: 10.1002/ptr.5381
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidant Effect of Fermented Papaya Preparation in the Oral Cavity

Abstract: Oxidative stress has been recognized to play important roles in various diseases, including of the oral cavity. However, nutritional supplementation of antioxidants to ameliorate the consequences of oxidative stress is debatable. One caveat is that oxidative status is often measured under non-physiological conditions. Here, we investigated the antioxidant potential of fermented papaya preparation (FPP), a product of yeast fermentation of Carica papaya Linn, under conditions that prevail in the oral cavity. Emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…In a study by Fibach and Ginsburg, the authors pointed out that an individual's oxidative stress level has an influential role to play in the health status of their oral cavity. Employing two highly sensitive luminol-dependent chemiluminescence assays, the authors demonstrated that under pathological conditions, FPP could easily dissolve in saliva or red blood cells to augment their antioxidant capacities [7]. The study conducted by our group and reported in Somanah et al [33] clearly supports this theory, and hence FPP may have a role in oral health benefits.…”
Section: Oral Health Challenges Amongst the Diabetic Community: Examisupporting
confidence: 59%
See 1 more Smart Citation
“…In a study by Fibach and Ginsburg, the authors pointed out that an individual's oxidative stress level has an influential role to play in the health status of their oral cavity. Employing two highly sensitive luminol-dependent chemiluminescence assays, the authors demonstrated that under pathological conditions, FPP could easily dissolve in saliva or red blood cells to augment their antioxidant capacities [7]. The study conducted by our group and reported in Somanah et al [33] clearly supports this theory, and hence FPP may have a role in oral health benefits.…”
Section: Oral Health Challenges Amongst the Diabetic Community: Examisupporting
confidence: 59%
“…Although the exact mechanism has yet to be understood, the authors speculate that FPP can work in synergy with human granulocytes to enhance the phagocytosis of key microorganisms present in gingival tissues [62]. capacities [7]. The study conducted by our group and reported in Somanah et al [33] clearly supports this theory, and hence FPP may have a role in oral health benefits.…”
Section: Oral Health Challenges Amongst the Diabetic Community: Examisupporting
confidence: 52%
“…The mode of topical oral application of SFPG we used in the present study showed more pronounced local anti-inflammatory and antimetabolic effects than the systemic ones (compare Figure 2(a) with Figure 2(b) and Figure 3 with Figure 4 ). Recent publication [ 52 ] has reported that saliva and its major components, such as albumin and mucin, substantially increase antioxidant capacity of another fermented papaya preparation by solubilisation of plant-derived polyphenols. It could be also assumed that a combination of intragingival with oral dietetic administration of SFPG to patients with periodontitis could better alleviate generalised chronic inflammation and connected metabolic disorders caused by the oral pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Secretion of copious amounts of saliva in the mouth by FPP would therefore rapidly clear any large food debris and encourage the buccal pH to return to baseline. In a study by Fibach and Ginsburg [9], the authors pointed out that an individual's oxidative stress level has an influential role to play on the health status of their oral cavity. Employing two highly sensitive luminol-dependant chemiluminescence assays, the authors demonstrated that under pathological conditions FPP could easily dissolve in saliva or red blood cells to augment their antioxidant capacities-possibly by increasing the solubility and availability of polyphenols present in the FPP.…”
Section: Examining the Anti-cariogenic Potential Of Fppmentioning
confidence: 99%
“…Initial fractionation of FPP by Rimbach et al [8] brought to light the different activity patterns of high and low molecular weight fractions with respect to superoxide anion scavenging and macrophage RAW 264.7 activation. Interestingly, Fibach and Ginsburg [9] pointed out that although the overall quantity of phenols in FPP is very low when measured in a salt solution, its levels can be boosted six-fold when assayed in saliva, albumin, mucin or red blood cell suspensions, possibly owing to its ability to pass through cell membrane barriers. Chemical analysis by Japanese researchers on a fermented papaya preparation using capillary electrophoresis-time-offlight mass spectrometry (CE-TOFMS) and liquid chromatography (LC-TOFMS) revealed several low-molecular weight phenolic acids, such as 2,5 dihydroxybenzoic acid, quinic acid, shikimic acid and m-amniophenol [10].…”
Section: Introductionmentioning
confidence: 99%